Does Gold Price Lead or Lags Islamic Stock Market and Strategy Commodity Price? A Study from Malaysia - Ibrahim, Siti Nurulhuda; Hasan, Rahayu; Nor, Amirudin Mohd (International Journal of Business, Economics and Management, 2018)
There is a few claimed in literature and financial media that gold, Islamic stock and commodity market provide as hedging tool against inflation. Therefore, derive from this similarity characteristic, we are interested to know which among of this investment variety are the leader and laggard in the Malaysian market. Among of them, numerous studies have been done on gold as a hedge against inflation, but almost non-existence amount of research endeavor to analyze the lead-lag of this precious metal with other investment avenues. Thus, several methods are employed to answer the issue of this study which are unit root tests and Johansen’s cointegration test, followed by long-run structural modelling (LRSM) and vector error-correction modelling (VECM), variance decompositions (VDCs), impulse response functions (IRFs) and persistence profile (PP). The results showed that spot Kijang Gold lags all investment avenues in Malaysia. It indicated that the performance of the Kijang Gold is dependent on FTSE Bursa Malaysia Emas Shariah Index, macroeconomic variables and strategic commodities. This provides some important policy implications in the regulation of the Kijang Gold itself whereby FTSE Bursa Malaysia Emas Shariah Index performance and other variables are among the key predictive inputs on the expected performance of the Kijang Gold. Hence, we humbly suggest to the investors and investment portfolio managers to include Islamic shariah equities, crude palm oil and crude oil commodities as part of their investment portfolios as may act as diversification and hedging tool especially for an investment portfolio which consists of Kijang Gold and forex, as we had identified these latter investment avenues as the most follower (endogenous) variables.